Does majority voting improve board accountability? - Stephen J. Choi; Jill E. Fisch; Marcel Kahan; Edward B. Rock (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
Directors have traditionally been elected by a plurality of the votes cast. This means that in uncontested elections, a candidate who receives even a single vote is elected. Proponents of "shareholder democracy" have advocated a shift to a majority voting rule in which a candidate must receive a majority of the votes cast to be elected. Over the past decade, they have been successful, and the shift to majority voting has been one of the most popular and successful governance reforms. Yet critics are skeptical as to whether majority voting improves board accountability. Tellingly, directors of companies with majority voting rarely fail to receive majority approval - even more rarely than directors of companies with plurality voting. Even when such directors fail to receive majority approval, they are unlikely to be forced to leave the board. This poses a puzzle: why do firms switch to majority voting and what effect does the switch have, if any, on director behavior? We empirically examine the adoption and impact of a majority voting rule using a sample of uncontested director elections from 2007 to 2013. We test and find partial support for four hypotheses that could explain why directors of majority voting firms so rarely fail to receive majority support: selection; deterrence/accountability; electioneering by firms; and restraint by shareholders. Our results further suggest that the reasons for and effects of adopting majority voting may differ between early and later adopters. We find that early adopters of majority voting were more shareholder-responsive than other firms even before they adopted majority voting. These firms seem to have adopted majority voting voluntarily, and the adoption of majority voting has made little difference in their responsiveness to shareholders responsiveness going forward. By contrast, for late adopters, we find no evidence that they were more shareholder-responsive than other firms before they adopted majority voting, but strong evidence that they became more responsive after adopting majority voting. Differences between early and late adopters can have important implications for understanding the spread of corporate governance reforms and evaluating their effects on firms. Reform advocates, rather than targeting the firms that, by their measures, are most in need of reform, instead seem to have targeted the firms that are already most responsive. They may then have used the widespread adoption of majority voting to create pressure on the nonadopting firms. Empirical studies of the effects of governance changes thus need to be sensitive to the possibility that early adopters and late adopters of reforms differ from each other and that the reforms may have different effects on these two groups of firms.
urn:nbn:de:hebis:30:3-420712
Keywords: 330